Analyses of learning motivation as a basis for learning and cognitive activity of students (Pedagogy of Higher and Secondary Education, 2013)
Stupak Z. I. Analyses of learning motivation as a basis for learning and cognitive activity of students.On the basis of analysis of learning motivation as a basis for learning and cognitive activity of students attempted to identify factors that influence the choice of future profession, as well as the motivation of learning activities of students.
Keywords: motives; motivation; motivational activities; needs; the process of learning